DAMPs and Innate Immune Training - Jentho, Elisa; Weis, Sebastian (Frontiers in Immunology, 2021)
The ability to remember a previous encounter with pathogens was long thought to be a key feature of the adaptive immune system enabling the host to mount a faster, more specific and more effective immune response upon the reencounter, reducing the severity of infectious diseases. Over the last 15 years, an increasing amount of evidence has accumulated showing that the innate immune system also has features of a memory. In contrast to the memory of adaptive immunity, innate immune memory is mediated by restructuration of the active chromatin landscape and imprinted by persisting adaptations of myelopoiesis. While originally described to occur in response to pathogen-associated molecular patterns, recent data indicate that host-derived damage-associated molecular patterns, i.e. alarmins, can also induce an innate immune memory. Potentially this is mediated by the same pattern recognition receptors and downstream signaling transduction pathways responsible for pathogen-associated innate immune training. Here, we summarize the available experimental data underlying innate immune memory in response to damage-associated molecular patterns. Further, we expound that trained immunity is a general component of innate immunity and outline several open questions for the rising field of pathogen-independent trained immunity.